Dead water [compact disc, unabridged] : a Shetland mystery - Cleeves, Ann (Cleeves, Ann. Shetland series, 2014)
When the body of a journalist is found, Detective Inspector Willow Reeves is drafted to head up the investigation. Inspector Jimmy Perez's local knowledge is needed in this case, and he decides to help Willow. The dead journalist had left the islands years before to pursue his writing career. In his wake, he left a scandal involving a young girl. When Willow and Jimmy dig deeper, they realize that the journalist was chasing a story that many Shetlanders didn't want to come to the surface.